Makna Syukur Dalam Perspektif Mufassir al-Qusyairi - Mairizal, T.; Marwah, Siti (Seutia Hukamaa Cendekia, 2023)
Within the Quran, the directive to convey appreciation is closely linked with the directive to engage in the remembrance of Allah (zikr), underscoring the importance of the role of gratitude. Scholars, particularly those within the Sufi tradition, exhibit diversity in their interpretations of gratitude, yet they collectively aim to consecrate all gifts from Allah exclusively to the path that pleases Him. To further comprehend the core of gratitude, this composition seeks to probe into Imam al-Qusyairi's perspective on the concept within the Tafsir Lathaif al-Isyarat. Utilizing a descriptive-analytical approach rooted in content analysis, al-Qusyairi's stance on gratitude can be distilled into two key points: the fundamental meaning of gratitude and how gratitude is expressed. The gratitude of a servant involves praising Allah and consistently recalling the kindness bestowed upon them, applying it in ways that align with Allah's pleasure. Conversely, the gratitude ascribed to Allah encompasses praising and recognizing His servants who have performed virtuous acts in obedience to Him. Modes of expressing gratitude can manifest through verbal articulation, physical deeds, and sincere sentiments, each corresponding to distinct levels of gratitude.